Epidemiology of knee injuries among U.S. high school athletes, 2005/2006-2010/2011 - Swenson, D. M.; Collins, C. L.; Best, T. M.; Flanigan, D. C.; Fields, S. K.; Comstock, R. D. (Medicine & Science in Sports & Exercise, 2013)
Purpose: U.S. high school athletes sustain millions of injuries annually. Detailed patterns of knee injuries, among the most costly sports injuries, remain largely unknown. We hypothesize that patterns of knee injuries in U.S. high school sports differ by sport and sex.